Hans Lindquist, Corpus Linguistics and the Description of English (Edinburgh University Press, 2009): a Detailed Evaluation - Marlies Prinzl (Opticon1826, 2010)
In Corpus Linguistics and the Description of English Hans Lindquist offers another introductory book to corpus linguistics, but aims it specifically at ‘university students of English at intermediate to advanced levels who have a certain background in grammar and linguistics, but who have not had the opportunity to use computer corpora to any great extent’ (Lindquist 2009, xvi). He proposes that the book, especially certain sections of it, may also be of interest to students of literature. Corpus Linguistics and the Description of English comprises ten chapters. Chapters 1-5 cover the basics, introducing corpus linguistics as a discipline, discussing its methods and explaining key terms, while Chapter 6-10 delve into more specific and different subject matters ranging from corpus-based metaphor studies to the applications of corpora in sociolinguistics. Readers new to corpus linguistics would therefore benefit from reading the first section of the book, but might opt to peruse only chapters relevant to their studies from the second part. That said, Chapters 6-10 provide a valuable overview of the different possibilities within corpus linguistics for anyone new to the field. All chapters are set up in an identical fashion and include, in addition to a discussion of the topic covered, a chapter summary, study questions, suggestions for further reading as well as online corpus exercises on the books supplementary webpage.